2020
DOI: 10.1002/cb.1875
|View full text |Cite
|
Sign up to set email alerts
|

Self‐determination, clean conscience, or social pressure? Underlying motivations for organic food consumption among young millennials

Abstract: The present world has led in individuals to become ever more interested in the consumption of organic food. Accordingly, companies are incorporating these worries in their managerial decisions by paying special attention to market segmentation. In this context, a relevant target audience is that conformed by young Millennials, a group defined by its growing purchase power, its intense influence on societies, but also by its inconsistency in terms of pro‐environmental behaviors. In order to understand the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 83 publications
(111 reference statements)
2
28
0
1
Order By: Relevance
“…When a sense of collectivism is activated, consumers are more likely to be influenced by norms (such as how others expect them to act) rather than the attributes of the product itself (White and Simpson, 2013; Li, 2020; Sahelices et al , 2020), that is, they are more concerned about their relationship with others around them (Kopania, 2020). In this situation, the consumption of organic food is one of dependence, so the presence of others and altruistic advertising appeal may change consumers' organic food purchase intention.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a sense of collectivism is activated, consumers are more likely to be influenced by norms (such as how others expect them to act) rather than the attributes of the product itself (White and Simpson, 2013; Li, 2020; Sahelices et al , 2020), that is, they are more concerned about their relationship with others around them (Kopania, 2020). In this situation, the consumption of organic food is one of dependence, so the presence of others and altruistic advertising appeal may change consumers' organic food purchase intention.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…From the altruistic perspective, buying organic food is an environmentally friendly behaviour. Considering that face consciousness is contextually relevant (Grant and Mayer, 2009), altruistic advertising appeal implies higher social expectations, based on which consumers may prefer to engage in more acceptable purchase behaviour by others, such as buying organic food (Sahelices et al , 2020). Thus, advertising appeal is taken as the other moderator to examine the boundary conditions of the relationship between face consciousness and organic food purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…Social status was often found to be a determinant influencing people's decisions to consume green products rather than their more luxurious, non-green counterparts [65]. Similarly, Sahelices-Pinto et al [66] showed that the consumption of organic foods was influenced by both social factors and self-esteem, revealing the impact of organic consumption on boosting one's social identity. Thus, hypothetically, a positive relationship may be established between social lifestyle and consumers' intentions to purchase organic foods (Hypothesis 4 (H4)).…”
Section: Social Lifestylementioning
confidence: 99%
“…Although age has been utilised in cases of market segmentation (Ivanova et al, 2019), it has been of limited use for understanding consumer behaviour deeper (Parment, 2013). Recently, an increasing interest in generational analysis is observed (Sahelices‐Pinto et al, 2020). A generational cohort has been considered to be a group of individuals, who were born during a limited period of time and share some characteristics and historical experiences (Rindfleisch, 1994).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Consumers aged 18 to 34 form generation Y, also called the Millennials (Lu et al, 2013; Sahelices‐Pinto et al, 2020). Although economic crisis delayed Millennials' entrance to the workforce, there are claims that they are expected to have higher incomes in the future compared to previous generations (Kanchanapibul et al, 2014; Kotler et al, 2017; Muralidharan & Xue, 2016; Sahelices‐Pinto et al, 2020), at least in the Western and emerging economies. From the income point of view, Millennials are expected to constitute a consumer segment that might contribute to the growth of green consumption (Fischer et al, 2017).…”
Section: Theoretical Perspectivementioning
confidence: 99%